Co-existential justice and individual freedom: the primary concern and the normative foundation of global ethics - Deng, An-qing (Journal of global ethics, 2025)
In the discussion of global ethics, philosophical ethics risks losing its distinct theoretical horizons. This predicament arises primarily from philosophy's failure to anchor its own object and to provide a rational basis for global justice from within its current confined theoretical paradigm. Against this background, this paper will first prioritize global co-existence as the primary concern of global ethics, then propose ontological co-existence justice as its foundational principle, and finally argue that the normative validity of co-existence justice is predicated on the nations fulfilling the critical requirements of modern civilization, namely, the advancement of individual freedom.